(untitled) (REMUNOM, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects cognitive ability, social interaction, and communication to varying degrees. This study aimed to evaluate and correlate the nutritional status (NS), physical activity level (PAL), risk of intestinal dysbiosis (RID), food consumption, and age group of children and adolescents with ASD from a neurological rehabilitation center in the municipality of Belém-PA. This is a quantitative, cross-sectional, descriptive, exploratory, and analytical study. Data were collected via Google Forms and statistically analyzed using the Pearson test and logistic regression model. The study included 42 individuals aged 6 to 17 years, with a predominance of males (73.81%) and an average age of 11 years. Regarding PAL, 50.00% of participants were considered physically active. As for RID, 64,29% presented a medium risk. In terms of NS, 50.00% of children were classified as obese, while 60.00% of adolescents were eutrophic. A high frequency of processed food consumption and a low intake of healthy foods were observed. Adolescents showed a higher likelihood of having an adequate NS compared to children. Thus, the analyses suggest a significant association between NS, RID, and age group, with the latter being the only variable with statistical significance in relation to nutritional status (p-value<0.05), highlighting that, in childhood, there was a 5.191 times higher likelihood of an inadequate nutritional status compared to adolescents. In the dietary context, there was a tendency toward the consumption of processed foods, often associated with natural and traditional foods from the studied region.